2009
DOI: 10.1242/jeb.031401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and dietary sterol availability on growth and cholesterol allocation of the aquatic keystone speciesDaphnia

Abstract: SUMMARYEnhanced water temperatures promote the occurrence of cyanobacterial blooms, which may be detrimental to aquatic herbivores. Especially, the often-dominant crustaceans could be negatively affected because cyanobacteria are deficient in phytosterols, which are required by the crustaceans to form the membrane component cholesterol, which in turn plays a role in thermal adaptation. Here, we determined the influence of temperature on growth, reproduction and the allocation of dietary sterol into somatic tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
47
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 53 publications
8
47
2
Order By: Relevance
“…So far, no study combined the effects of food quality and temperature across generations as we have done in our experiment. Sperfeld and Wacker (2009) found a higher demand for cholesterol for growth at higher temperatures. They also found that mothers invested more cholesterol into eggs at higher temperatures but only if dietary cholesterol content was not limiting (Sperfeld and Wacker 2009).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…So far, no study combined the effects of food quality and temperature across generations as we have done in our experiment. Sperfeld and Wacker (2009) found a higher demand for cholesterol for growth at higher temperatures. They also found that mothers invested more cholesterol into eggs at higher temperatures but only if dietary cholesterol content was not limiting (Sperfeld and Wacker 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Sperfeld and Wacker (2009) found a higher demand for cholesterol for growth at higher temperatures. They also found that mothers invested more cholesterol into eggs at higher temperatures but only if dietary cholesterol content was not limiting (Sperfeld and Wacker 2009). Cholesterol content of maternal diet may therefore be expected to affect offspring quality more strongly at higher temperatures.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations